Clinical features of SMARCA2 duplication overlap with Coffin–Siris syndrome. Issue 10 (5th June 2016) - Miyake, Noriko; Abdel‐Salam, Ghada; Yamagata, Takanori; Eid, Maha M.; Osaka, Hitoshi; Okamoto, Nobuhiko; Mohamed, Amal M.; Ikeda, Takahiro; Afifi, Hanan H.; Piard, Juliette; van Maldergem, Lionel; Mizuguchi, Takeshi; et al.
Abstract : Coffin–Siris syndrome is a rare congenital malformation and intellectual disability syndrome. Mutations in at least seven genes have been identified. Here, we performed copy number analysis in 37 patients with features of CSS in whom no causative mutations were identified by exome sequencing. We identified a patient with a 9p24.3–p22.2 duplication and another patient with the chromosome der(6)t(6;9)(p25;p21)mat. Both patients share a duplicated 15.8‐Mb region containing 46 protein coding genes, including SMARCA2 . Dominant negative effects of SMARCA2 mutations may contribute to Nicolaides–Baraitser syndrome. We conclude that their features better resemble Coffin–Siris syndrome, rather than Nicolaides–Baraitser syndrome and that these features likely arise from SMARCA2 over‐dosage. Pure 9p duplications (not caused by unbalanced translocations) are rare. Copy number analysis in patients with features that overlap with Coffin–Siris syndrome is recommended to further determine their genetic aspects. © 2016 Wiley Periodicals, Inc.